2006
DOI: 10.1021/nl060563u
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of Guanine and Cytosine on Graphite:  Ordered Structure Based on GC Pairing

Abstract: Nanostructures formed by coadsorption of the complementary DNA bases guanine (G) and cytosine (C) at a graphite surface in 1-octanol solvent were investigated by in situ scanning tunneling microscopy. The high-resolution observations showed for the first time a well-ordered coadsorption structure, attributed to rows formed from Watson-Crick G-C pairs, which was distinctly different from the structures observed for the individual G/C components. The observed coadsorption structure has been modeled by self-consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
92
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 46 publications
6
92
0
Order By: Relevance
“…[20] In the recent years, a number of groups have carried out studies on how different nucleobases and nucleobase pairs self-assemble on a surface. [21,[31][32][33] The molecular self-assembly involving adsorption of nucleic acid bases on a graphite surface has been characterized by different spectroscopic techniques. The nucleobases self-assemble to form monolayers that are stabilized by hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[20] In the recent years, a number of groups have carried out studies on how different nucleobases and nucleobase pairs self-assemble on a surface. [21,[31][32][33] The molecular self-assembly involving adsorption of nucleic acid bases on a graphite surface has been characterized by different spectroscopic techniques. The nucleobases self-assemble to form monolayers that are stabilized by hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several successful attempts have been reported to grow organic layers with designed structures by influencing the intermolecular interactions, which are accessible i) by the choice of molecules exhibiting complementary functional groups with the potential to form hydrogen bonds, [5][6][7][8] ii) by the addition of metallic atoms to the surface that induce the formation of metalloorganic networks, [9][10][11][12] or iii) by thermally activating chemical reactions between predetermined molecular connection points. [13,14] With the same purpose, it has also been demonstrated that the moleculesubstrate interactions can be influenced by the use of nanostructured surfaces, such as those resulting from surface superstructures or stepped surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Systems based on planar molecules have been reported to build up the same bonding motifs in 2D as well as in 3D environments both for homomolecular [8][9][10] and for heteromolecular cases. [5,6,11] The resulting surface-confined architectures are influenced by the substrate on which the assembly takes place. [12] The wide range of possible substrate-induced effects spans from moderate quantitative variations to qualitatively new ordering behavior.…”
Section: Introductionmentioning
confidence: 99%